Adsorption Kinetics, Equilibrium, and Thermodynamics of Copper From Aqueous Solutions using Silicon Carbide Derived from Rice Waste. Issue 2 (1st February 2016) - Taha, A. A.; Ghani, S. A. Abdel
Abstract : Adsorption of Cu(II) from aqueous solution on a novel adsorbent, silicon carbide ash (SiC ash), was studied using batch technique. The adsorbent was prepared by pyrolysis of Egyptian rice waste (rice straw and rice husk) and was characterized by scanning electron microscopy (SEM), energy-dispersive x-ray (EDX), Fourier-transform infrared (FTIR) spectroscopy, x-ray diffraction (XRD), and surface area analysis by Brunauer-Emmett-Teller (BET) Theory. The influence of pH, contact time, initial Cu(II) concentration, adsorbent dose, agitation speed, and temperature was investigated. Adsorption kinetics was analyzed using the pseudo-first-order, the pseudo-second-order, and intraparticular diffusion model. The adsorption process was found to follow a pseudo-second-order rate mechanism. The adsorption isotherm data could be well described by the Langmuir and Freundlich than the Dubinin–Radushkevich adsorption model. The adsorption capacity of 22.06 mg g −1 for SiC ash was obtained at pH = 5 and temperature of 298 K. Thermodynamic parameters, change in the free energy (Δ G °), the enthalpy (Δ H °), and the entropy (Δ S °), were also calculated. The overall adsorption process was exothermic, spontaneous in nature, and proceeds with decreased randomness as the entropy is negative value. Adsorption process was successfully applied to remove Cu(II) from an industrial wastewater sample. GRAPHICAL ABSTRACT: